Percepción del vínculo de las prácticas docentes con el desencadenamiento y mantenimiento de los intereses personales de ex alumnos de colegios de Lima Metropolitana - Borges de Sanctis, Francisco (2021)
The present research, based on the qualitative paradigm, aims to identify the perceptions of former students on the link of teacher practices with the triggering and maintenance of their personal interests. In order to achieve this goal, individual and group interviews were applied to 17 graduates from two private schools from Lima Metropolitana, one only for men and another only for women, seeking variety of personal interests between participants. Results allowed to recognize that participants perceive that teacher practice link with the triggering and maintenance of their personal interests through scholar activities that offer new information and a social environment that supports relation, autonomy and competence. By contrast, the perception of the interviewees did not link the educational environment with the triggering and maintenance of their personal interests. Finally, the participants consider that school time experiences have endured over time and link to experiences of other social environments.